Bagong bagoong empowering the coastal community in Tangos, Navotas - Valderrama, Joel Bienne M.; Melgazo, Dylan James L. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
The Bagong Bagoong is a new urban center which is envisioned to enable a high-density coastal community in Navotas. It is located in Barangay Tangos which is the most dense barangay in the city. The high-density community at the end of the M. Naval Street is the main area of intervention for this project. Generally, it is amized-use residential area known for its major industry - bagoong alamang. Despite this, the community is still experiencing poverty. This project is envisioned to help the community in alleviating poverty and be enabled to have a more productive and sustainable living. This will be achieved through the design strategies that will create a framework for development. These design strategies are: urban linkages, livelihood development, educational support, and community empowerment. With these strategies, the general spaces of the development are identified. The project is livelihood-centric, multi functional community development with manufacturing and processing facilities, a market, a community library, training and workshop facilities, and civic spaces.
Include appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: City planning -- Navotas City -- Philippines